EFEKTIVITAS METODE MIMICRY MEMORIZATION BERBANTUAN MEDIA GAMBAR TERHADAP PENGUASAAN KOSAKATA BAHASA ARAB - Khaerunnisa, Nur Azizah; Maria, Enung; Hasmawati, Hasmawati (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to determine the effectiveness of mimicry memorization method assisted by picture media on Arabic vocabulary mastery. The design used in this research is non-equivalent control group by using quantitative methodology which is experimental. The research population was grade IV students of SD IT Al-Madinah Maros as many as 90 students and the research sample was grade IVC students as many as 22 students became the experimental class and grade IVD students as many as 22 students became the control class selected by purposive sampling technique. The research data collection technique was carried out by giving instruments in the form of pretests and posttests. The data analysis techniques used were descriptive analysis and inferential analysis. Based on the results of hypothesis test calculations with alpha 0.05 or 5%, the tcount ttable value or 3.15 2.018, then the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. Thus, it can be concluded that the mimicry memorization method assisted by image media is effective on the mastery of Arabic vocabulary of fourth grade students of SD IT Al-Madinah Maros.